"Get off the sofa and go and play": Family and socioeconomic influences on the physical activity of 10-11 year old children - Thompson Janice L; Fox Kenneth R; Jago Russell; Brockman Rowan; Cartwright Kim; Page Angie S (BMC, 2009)
Abstract Background Physical activity declines as children approach puberty. Research has focussed on psychosocial, environmental, and demographic determinants. This paper explores how family and socioeconomic factors are related to children's physical activity. Methods Seventeen focus groups were conducted with 113, 10-11 year old children from 11 primary schools in Bristol, UK. Focus groups examined: 1) the way parents encourage their children to be physically active; 2) the extent to which physical activity is engaged in as a family; and 3) the types of non-family based physical activities Year 6 children commonly participate in. Results Participants from all socioeconomic (SES) groups reported that parents encouraged them to be physically active. However approaches differed. Children from middle/high SES schools were assisted through actions such as logistical and financial support, co-participation and modelling. Parents of children from low SES schools mainly restricted their input to verbal encouragement and demands. Participation in family-based activities was reported to be higher in children from middle/high SES schools than children from low SES schools. All SES groups reported time to be a limiting factor in family-based activity participation. Cost was reported as a significant barrier by children from low SES schools. Children from middle/high SES schools reported engaging in more sports clubs and organised activities than children from low SES schools, who reported participating in more unstructured activities or 'free play' with friends. Conclusion The family is important for encouraging children to be physically active, but families from different socioeconomic backgrounds support their children in different ways. This research suggests that the design of physical activity interventions, which might include working with families, requires tailoring to groups from different socio-economic backgrounds.